PEDAGOGICAL CONDITIONS FOR DEVELOPING STUDENTS’ COMPARATIVE THINKING THROUGH FABLES (Global Conference on Medical and Health Sciences, 2026)
Pedagogical conditions for the formation of comparative thinking in students through parables are an area that requires special attention and in-depth analysis as one of the urgent issues in today's education system. As is known, the experience of the education system of developed countries shows that not only knowledge itself, but also the ability to think deeply, to compare each fact and phenomenon with other facts and phenomena, to have an independent opinion, to analyze and generalize them according to certain criteria are among the main competencies for a modern person.Therefore, in pedagogical activity, especially at the higher education stage, it is important to develop comparative thinking skills at a high level in order to form students not only with scientific knowledge, but also as specialists with developed multi-competent, analytical and creative thinking.
Keywords: Parables, comparative thinking, pedagogical conditions, thinking in students, educational environment, interactive methods, analytical competence, modern educational process, critical thinking, independent analysis.